CYP2D6 Metabolizer Status and Mortality in Metoprolol Users - Simon de Denus; Essaïd Oussaïd; Maxime Meloche; Antoine‐Xavier Bertrand; Grégoire Leclair; Marie‐Christyne Cyr; Martin Jutras; Marie‐Josée Gaulin; Ian Mongrain; David Busseuil; Jean‐Claude Tardif; Marie‐Pierre Dubé (Clinical and Translational Science, 2026)
ABSTRACT Numerous pharmacogenomic (PGx) associations of pharmacokinetics and pharmacodynamics of commonly prescribed medications have been reported. Yet, the evidence supporting their association on survival remains underexamined. We sought to investigate the CYP2D6 ‐metoprolol association and determine whether the established variability in drug exposure and hemodynamic response would translate into differences in mortality across metabolizer status in the Montreal Heart Institute Hospital Cohort. Single random plasma samples were collected from 996 patients receiving metoprolol tartrate. Bioanalytical quantification was performed via liquid chromatography–tandem mass spectrometry, while CYP2D6 metabolizer status was based on standardized classifications. Cox regression models adjusted for age, sex, cardiovascular history, concomitant medications, and CYP2D6 inhibitors were used to assess the time to death since enrolment. Overall, 24.3% ( n = 242) of patients were deceased at follow‐up (median 101.4 months). Higher metabolizer status at CYP2D6 was associated with lower risk of death (HR = 0.82, 95% CI: 0.67–0.99; p = 0.04). Metoprolol concentrations were no longer associated with mortality after adjusting for possible confounders. Our study suggests that CYP2D6 ‐inferred metabolizer status can inform on mortality risk in patients treated with metoprolol. Larger initiatives are required to confirm the association of CYP2D6 metabolizer status with clinical events beyond pharmacokinetic and hemodynamic considerations.